Economic benefits comparison between point‐to‐point and multi‐terminal VSC HVDC systems with large‐scale wind farms. Issue 11 (30th May 2018) - Kim, Sangwon; Yokoyama, Akihiko; Takano, Tomihiro; Izui, Yoshio; Hashimoto, Hiroyuki
Abstract : From the economic viewpoint, multi‐terminal voltage‐source converter high voltage direct current (VSC HVDC) transmission system configurations have many advantages over point‐to‐point VSC HVDC systems in large‐scale wind power transmission scenarios. In these scenarios, the economic benefits comparison between point‐to‐point and multi‐terminal VSC HVDC systems based on the security‐constrained optimal power flow analysis is the main target of this paper. It is revealed that compared to point‐to‐point VSC HVDC systems, the proposed multi‐terminal VSC HVDC systems have the following economic benefits. More effective economic load dispatch can be achieved. In addition, the wheeling charge produced by the multi‐terminal VSC HVDC systems is also higher due to the higher multi‐terminal VSC HVDC systems' capacity factor. The lower fuel costs and higher wheeling charge of the multi‐terminal VSC HVDC systems are reflected in the annual cash inflow. The economic benefits of the multi‐terminal VSC HVDC systems are proved by calculating the higher Net Present Value (NPV) and Profitability Index (PI) values of the systems. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.